Stand dynamics, spatial pattern and site quality in Austrocedrus chilensis forests in Patagonia, Argentina - Burns, Sarah Lilian (2013)
Aim of study: The objective of this study was to analyze the stand structure and spatial pattern of two A. chilensis stands with contrasting soil conditions and different site qualities in order to explore if these differences lead to patterns similar to the ones observed under different precipitation conditions. Area of study: The study was carried out in two stands located near the city of El Bolsón (41° 56’S - 71° 33’ W), Rio Negro, Argentina. Material and methods: We evaluated age difference between canopy strata (upper and lower) in two stands with different site qualities by means of a Mann-Whitney test. Dead individuals by diameter class were compared by means of a chi square test. Spatial distribution pattern was analyzed using the pair-correlation function and the mark-correlation function. Main results: Both sites exhibited a random spatial distribution of A. chilensis but different processes seem to underlie the patterns. In the low-quality site facilitation and continuous establishment led to a transient clumped spatial pattern. Mortality mediated by competition occurred mainly on small trees resulting in the current random pattern. On the other hand, spatial pattern in the high-quality site does not reflect a facilitation mediated recruitment. The upper strata established synchronously and subsequent regeneration was episodic. Research highlights: The results show that the differences in site quality may lead to different establishment spatial patterns, showing the importance of facilitation processes in sites with drier soil conditions and lower quality, although results may be site specific, due to the lack of replications.